Secrecy performance analysis of cell-free massive MIMO in the presence of active eavesdropper with low resolution ADCs - Zhang, Xianyu; Liang, Tao; An, Kang (Wireless networks, 2021)
This paper investigates the secrecy performance of the Cell-Free massive multiple-input multiple-output network with finite resolution analog-to-digital converters at the access points (APs) and users in presence of an active eavesdropper. Using the additive quantization noise model, the uplink minimum mean squared error channel estimation and downlink data precoding are respectively operated. Specifically, the lower bound on the achievable ergodic rate and upper bound for the information leakage to the eavesdropper are theoretically derived in details. Thereby, the closed-form expression for the achievable ergodic secrecy rate is accordingly obtained with respect to the number of APs, number of each APs antenna, number of users, pilot and data transmission power and quantization bits, etc. In addition, the asymptotic approximation for the ergodic secrecy rate has been presented. Moreover, the path-following power control algorithm has been proposed aiming at maximizing the secrecy rate subject to both power and achievable rate constraints. Finally, extensive simulations are provided to corroborate the theoretical analytical results and the validity of the proposed power allocation scheme.